Narrative Review of Anti-CD3 Antibody and Anti-CD20 Antibody: Immunotherapeutic Strategies to Treat and Prevent Type 1 Diabetes - Kashalikar, Prajakta; Desai, Shivani; Sanap, Avinash; Shekatkar, Madhura; Bhonde, Ramesh (Recent Advances in Inflammation & Allergy Drug Discovery, 2023)
Background and Objective: Type 1 diabetes mellitus is a complex disease defined by the loss of pancreatic cells, which leads to complete insulin insufficiency. The Diabetes Control and Problems Trial defines the aims of Type 1 diabetes therapy as achieving adequate glycaemic control, and preventing and avoiding recurrent bouts of hypoglycaemia. Despite ongoing efforts to improve insulin therapy regimens, the actual hormone substitute therapy treats just the symptoms of the disease, with no influence on disease pathology or etiopathogenesis. In recent decades, there has been a lot of interest in preventative techniques in high-risk patients, based on the theory that if a therapeutic intervention is adopted early in the disease, it can help maintain endogenous cell function by protecting the remaining cell reservoir from autoimmune attack. Methods: Based on preclinical and clinical data, we have discussed some immunotherapeutic in this meta-analysis. We referred to the preclinical and clinical studies for teplizumab and rituximab from authentic databases and compiled the data. We used statistical analysis to do a meta-analysis. Results: In two immunotherapeutic anti-CD3 antibodies and anti-CD20 antibodies examples, teplizumab and rituximab, respectively, shows better efficacy as well as fewer side effects. We have discussed this drug briefly based on their mechanism of action and meta-analysis, which compare clinical efficacy. Conclusion: Immunotherapeutic can be a better option for preventing and protecting type one diabetes. Since, the existing literature does not have enough data to support any single drug concluding the same will not be appropriate. Hence further studies are required wherein different drugs can be compared with similar sample sizes for each group of drugs.
Keywords: teplizumab